Assessing the needs for quality neighbourhood parks - Abdul Malek, Nurhayati; Mariapan, Manohar; Mohd Shariff, Mustafa Kamal; Aziz, Azlizam (INSI Publications, 2011)
The understanding of needs aspect is important. A lot of people share common needs, but by identifying each person’s unique needs will help answer why people use a particular space in the first place. Various studies also confirms the link between high quality green spaces with the increased property value; benefits in improving the image of an area as to attract investment; contribution to biodiversity; contribution in promoting physical activities and the benefits to health; and finally overcoming the anti-social behavior through design and management. The purpose of this review paper is to help fill in gaps that more methods are required for evaluating projects so as to obtain high quality evidence for better outdoor recreational venues such as neighbourhood parks.This review suggests that natural settings, safety, aesthetic appeal, convenience, psychological comfort, and symbolic ownership, policy on use, cost and interaction with natural environment are significantly important to park users’ needs attributes relating to the design of a neighbourhood green open space. This paper provides a critical review of past and current research and its theoretical fundamentals on park users needs for a successful or a quality neighbourhood green open spaces. It should be of interest to landscape architects, park designers, urban designers, city planners, architects, developers as well as any other professional involved in the development of new residential neighbourhoods.